Akuntansi Syariah: Harapan dan Realitas di Lembaga Keuangan Syariah - Fani Febriani, Melsa; Dyah Pekerti, Retno (JURNAL EKONOMI PERJUANGAN, 2023)
This study aims to determine the influence of Islamic accounting knowledge, work environment, and religiosity on the interest of accounting students in a career in Islamic financial institutions. The population in this study was all accounting students at Cipasung Tasikmalaya University, which amounted to 418 people. The sample selection method uses non-probability sampling techniques. The research method used is a quantitative descriptive analysis method. for data analysis using the IBM SPSS Statistics 27 system program. The results of this study show that partially (t) the variable of religiosity does not have an influence on the interest of accounting students for a career in Islamic financial institutions, while the variables of Islamic accounting knowledge and work environment have an influence on the interest of accounting students for a career in Islamic financial institutions. Simultaneously, (f) Islamic accounting knowledge, work environment, and religiosity jointly affect the interest of accounting students in a career in Islamic financial institutions. The R square value of 0.461 means that the amount of independent influence on the dependent variable is 46.1%. While the remaining 53.9% was influenced by other variables that were not variables in this study.